If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) + 5x = 6x + 14 Reorder the terms: 3(2 + x) + 5x = 6x + 14 (2 * 3 + x * 3) + 5x = 6x + 14 (6 + 3x) + 5x = 6x + 14 Combine like terms: 3x + 5x = 8x 6 + 8x = 6x + 14 Reorder the terms: 6 + 8x = 14 + 6x Solving 6 + 8x = 14 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 6 + 8x + -6x = 14 + 6x + -6x Combine like terms: 8x + -6x = 2x 6 + 2x = 14 + 6x + -6x Combine like terms: 6x + -6x = 0 6 + 2x = 14 + 0 6 + 2x = 14 Add '-6' to each side of the equation. 6 + -6 + 2x = 14 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 14 + -6 2x = 14 + -6 Combine like terms: 14 + -6 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| -5m=20 | | 8a^2+2a-21= | | x+4.9=18.8 | | 15+17f-5f-16f= | | 12x-35x+18= | | (x^2)-(5x)+(y^2)-(3y)=1 | | x+4(x+2)=16 | | 5*[6*6]=10 | | 4a^2-5a-6= | | 5*[6*6]= | | -15t^2+45t+10=40 | | 5X[6*6]= | | -15t+75t+10=70 | | -15t+75t+10=100 | | 5x-10=-15 | | 6x=24-4(x-4) | | 2y^2+11y+12= | | 2x+1=131 | | 5e^3x=15 | | 14y+9y-2+y= | | 6+4x-4=9x+8-3x | | 8(3x-1)=-8+24 | | 23x+18=-24x-358 | | -4+6k=-34 | | 3(x-3)=3(x+3) | | g+15-4g-6g= | | m*9-1=-2 | | v+v-33.4+v+24.1=189.9 | | -3x-4+3x=-4 | | 3w^2-14w-5=0 | | -10=10(k+9) | | v=(v-31.4) |